Pruning Shade Trees in Landscapes: A Plan for Training Shade Trees - Edward F. Gilman (EDIS)
ENH-1022, a 3-page illustrated fact sheet by Dr. E. F. Gilman, lists the strategies for training shade trees and presents a pruning plan describing what to do at each of seven prunings in the first 25 years of planting. Published by the UF Department of Environmental Horticulture, December 2006.